Keragaman varietas lokal dan produksi pati sagu di Distrik Aranday, Kabupaten Teluk Bintuni - Baru, Yanuarius; Dimara, Petrus; Heatubun, Charlie D. (Cassowary, 2026)
The present study is designed to determine the diversity of sago (Metroxylon sagu Rottb.) the starch production potential of each variety in Aranday District, Teluk Bintuni Regency West Papua. This article adopts an exploratory–descriptive approach by incorporating morphological characterisation, local indigenous knowledge of Sebyar community and quantification starch yield. Three well-known local sago varieties were purposively taken, Bitanonggi, Ponggri and Kikitor as a sampling object with three replications for each variety. The findings concluded that a total of sago forest area in Aranday District amounted to 4,877.08 ha covering four villages and the highest domination by Aranday Village (53.84%). Based on morphological characteristics, the Bitanonggi variety had the largest stem diameter (44.0–52.7 cm) and the tallest height (10.4–18.0 m), followed by Ponggri (45.4–48.8 cm; 9.0–12.3 m) and Kikitor (42.0–49.5 cm; 8.5–11.8 m). Bitanonggi also produced the highest starch yield, with 296 kg of wet starch and 247.2 kg of dry starch per tree, followed by Ponggri (287 kg wet; 220.9 kg dry) and Kikitor (198 kg wet; 158.6 kg dry). Stem diameter and volume were revealed to be principal morphological traits controlling starch productivity. Taken together, the juvenile age structure of trees actively growing in Aranday sago groves suggest that considerable scope exists for sustainable food resource development. The results can be used as scientific basis to sustain the sago diversity and promote conservation and utilization of local sago varieties by ecological potential as well as indigenous knowledge.